2015
DOI: 10.1017/jfm.2015.112
|View full text |Cite
|
Sign up to set email alerts
|

The time evolution of the maximal horizontal surface fluid velocity for an irrotational wave approaching breaking

Abstract: We derive an equation that relates the evolution in time of the maximum of the horizontal fluid velocity at the surface of an irrotational deep-water plunging or spilling breaker to the first component of the pressure gradient at the surface. The approach applies to overhanging wave profiles, up to breaking time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 17 publications
(24 reference statements)
1
8
0
Order By: Relevance
“…Since the variation along the arc length σ is such that |U | goes on increasing as we approach the point 2, and given that the horizontal velocity |U | decreases dramatically at point 1, the maximum necessarily occurs in the vicinity of point 2. These results are quite in line with those of Constantin [6].…”
Section: Identification Of the Velocity At The Free Surfacesupporting
confidence: 93%
“…Since the variation along the arc length σ is such that |U | goes on increasing as we approach the point 2, and given that the horizontal velocity |U | decreases dramatically at point 1, the maximum necessarily occurs in the vicinity of point 2. These results are quite in line with those of Constantin [6].…”
Section: Identification Of the Velocity At The Free Surfacesupporting
confidence: 93%
“…Constantin & Strauss [14] proved that the pressure strictly decreases horizontally away from a crest line towards its neighbouring trough lines and increases with depth provided the maximum angle of inclination of the free surface is at most 45°. Recently, using an exact equation relating the time evolution of the maximum and minimum horizontal fluid velocities at the surface, Constantin [15] found that the derivative of the pressure is negative on the forward face of a wave, while it is positive on the rear face. More recently, Constantin [16] and Martin [17] proved mathematically that, for irrotational waves, the maximum and minimum of the dynamic pressure occur at the wave crest and wave trough, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Assuming the natural physical condition that initially the normal derivative of the pressure is negative on the smooth free surface, the short-time existence of a smooth subsequent free surface is ensured by the considerations in [12,31]. While the solution generated by such an initial state might develop into a breaking wave (see the discussion in [8]), in which case our considerations refer to any time up to the breaking time, it is known (see [24]) that small localized data ensure the longtime existence of solutions even outside the class of travelling waves. Let us also point out that smooth surface wave profiles of constant-vorticity flows are quite common: in particular, a travelling wave profile that is Hölder continuously differentiable must be real analytic (see [9]).…”
Section: The Mean Flow Beneath the Surface Wavesmentioning
confidence: 99%